To solve the equation \( 13x + 26 = 3x - 34 \), we can follow these steps:
-
Get all terms involving \( x \) on one side and constant terms on the other side.
Subtract \( 3x \) from both sides: \[ 13x - 3x + 26 = -34 \] This simplifies to: \[ 10x + 26 = -34 \]
-
Subtract 26 from both sides: \[ 10x = -34 - 26 \] This simplifies to: \[ 10x = -60 \]
-
Now, divide both sides by 10: \[ x = \frac{-60}{10} \] This simplifies to: \[ x = -6 \]
Thus, the solution is \( x = -6 \).
So, the correct response is: x = -6 (x equals negative 6).